MENGENAL NYERI PERSALINAN PADA PRIMIPARA DAN MULTIPARA - Ida Widiawati; Titi Legiati (Jurnal BIMTAS: Jurnal Kebidanan Umtas, 2019)
Uterine contractions causes complaints of labor pain, anxiety and fatigue in the mother of labor and has a negative influence on the progress of labor and fetal well-being. The results of the study showed that labor caused severe pain (91.9%) and the experience of pain caused a negative experience for women. So that midwives and women need to know and understand pain in labor. The aim of the study was to analyze labor pain in primiparas and multiparas. In this cross-sectional study, 55 women in labor participated. Pain labor intensity were measurement of numerical rating scale, data were analyzed using chi square. In this study, 63% primiparous women participated had severe pain, higher than multiparous women participants (37%). The chi square analysis results showed no significant relationship between parity and first stage labor pain p = 0.4 (> 0.05). It is important to understand and recognize the physiology of pain in the first and second stage of labor so that midwives can manage the management of labor pain in accordance with the physiological pathway. Accurate education about reducing labor pain must be informed during pregnancy to increase female self-esteem during labor. Further research is needed by increasing the number of samples, to be able to describe differences in pain during labor based on parity by adding psychological variables and physiology.